Integrative analysis of omics summary data reveals putative mechanisms underlying complex traits - Yang Wu (Nature Portfolio, 2018)
The identification of the causal gene at a GWAS locus remains to be a challenging task. Here, using the SMR & HEIDI method to integrate GWAS, eQTL and mQTL data, Wu et al. map DNA methylation sites to the transcriptome and thereby prioritize functionally relevant genes for 12 human complex traits.